Growth and mineral nutrition of Urochloa arrecta Crescimento e nutrição mineral de Urochloa arrecta - Bianco S. (2015)
© 2015 Sociedade Brasileira da Ciencia das Plantas Daninha. All Rights Received.The experiment was carried out aiming to analyze dry mass production and distribution, and the content and accumulation of macronutrients in Urochloa arrecta plants cultivated under mineral nutrition standard conditions. Plants grew in seven-liter pots filled with sand substrate, were daily irrigated with nutrient solution, and maintained under greenhouse conditions. Treatments corresponded to assessment periods (21, 35, 49, 63, 77, 91, 105, 119, 133, 147, and 161 days after emergence – DAE) and were arranged in a completely randomized design with four replicates. Plants of U. arrecta showed low accumulation (less than 7% of the maximum accumulation at 161 DAE) of dry mass (5.1 g DM per planta) and of macronutrients (57.7 mg N per planta, 8.9 mg P per planta, 167.8 mg K per planta, 21.3 mg Ca per planta, 14.7 mg Mg per planta, and 9.2 mg S per planta) up to 49 DAE. Such accumulations increased mainly after 91 DAE. Daily accumulation rate was crescent up to 130 DAE (DM and S), 137 DAE (N), 125 DAE (P), 119 DAE (K), 144 DAE (Ca), and 128 DAE (Mg), when there was accumulation of 87.7 g DM per planta, 918.0 mg N per planta, 105.8 mg P per planta, 1,643.9 K per planta, 390.4 mg Ca per planta, 200.0 mg Mg per planta, and 103.5 mg S per planta. K and N were found to have the highest rates and, hence, they were the most demanded and accumulated in the greatest amounts in U. arrecta plant tissues.